Network performance enhancement via MPLS traffic engineering / Ahmad Firdaus Abu Bakar - Abu Bakar, Ahmad Firdaus (Faculty of Information Technology and Quantitative Sciences, 2004)
The exponential growth of the Internet for the past few years has made the IP protocol suite the most predominant technology. In addition, the merge of voice and data communications over a single network infrastructure is expected to happen over IP-based network. Traditional IP networks offer little predictability of service, which is often unacceptable for applications such as telephony, as well as for emerging and future real-time applications such as telemedicine. One of the primary goals of traffic engineering is to enable networks to offer predictable performance. The Internet Engineering Task Force has developed standards for traffic engineering in IP-based networks. This project discusses the traffic engineering mechanisms developed by the IETF, how MPLS works as traffic engineering tool, and how MPLS deals with links and nodes failure.